Application of foreign legal norms in notarial activity during the years of independence (Eurasian Journal of Learning and Academic Teaching, 2022)
The article is devoted to the role of notarial activity in the international arena, legal norms governing the documents issued for service abroad, international documents of which our country is a member, the international notarial system.